ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (LKPD) PADA DINAS KESEHATAN DI KOTA MEDAN - Nasirwan Nasirwan; Ade Vani Meilani, Aprillia Siahaan, Ayona Artia Sitohang (CV. Adiba Aisha Amira, 2024)
One of the roles of public sector accounting is to enhance the quality of financial reporting. The purpose of this research is to understand the impact of leadership, personnel, and internal control systems on the quality of local government financial statements at the Medan City Health Department. The research method used is quantitative, with data collection carried out through questionnaires. The population and sample size used is 30 people. The data analysis technique applied is multiple linear regression. The research findings indicate that leadership, personnel, and internal control systems have a positive and significant impact on the quality of local government financial statements.